Investigation of the Effect of Astaxanthin on Autophagy in Renal Ischemia-reperfusion Modeled Rats - Aysegul KISAOGLU; Evren KOSE; Nesibe YILMAZ; Kevser TANBEK; Azibe YILDIZ; Umit YILMAZ; Rumeyza Hilal CIRIK; Davut OZBAG (Medeniyet Medical Journal)
Objective: The aim of this study was to investigate the effect of various astaxanthin (ATX) doses on oxidative damage and autophagy in renal ischemia-reperfusion (I/R) injury-modeled rats. Methods: The rats were divided into five groups: sham group (n=8), I/R (n=8), I/R + 5 mg/kg ATX (n=8), I/R + 10 mg/kg ATX (n=8), and I/R + 25 mg/kg ATX (n=8) groups. ATX was dissolved in 5 mg/kg, 10 mg/kg, and 25 mg/kg olive oil for 7 days and administered to the rats in the experimental group. Sham and I/R groups were also administered ATX solution (olive oil) via oral gavage for 7 days. Renal ischemia reperfusion was induced in all rats except the sham group after the last dose was administered on the 7th day. Reperfusion was conducted for 24 hours after 45 minutes of ischemia. Results: Blood samples were collected, and kidney tissue were incised for biochemical and histological analyses. Superoxide dismutase (SOD) and total antioxidant status (TAS) were significantly lower in the I/R group than in the sham group (p<0.05), whereas malondialdehyde (MDA) and total oxidant status (TOS) values were higher (p<0.05). It was determined that SOD and TAS increased and MDA and TOS decreased in the ATX-administration groups compared with the I/R group, independent of the dose (p<0.05). In the 25 mg/kg ATX + I/R group, Beclin-1 and LC3β immunoreactivities were significantly higher than those in the other groups (p<0.05). The lowest p62 immunoreactivity was observed in the 25 mg/kg ATX + I/R group. Conclusions: ATX had a protective effect on kidney function and against oxidative damage. Furthermore, high-dose ATX administration protected kidney tissue via autophagy induction in this study.